KESESUAIAN PUTUSAN HAKIM DALAM PERKARA ANAK SEBAGAI PERANTARA JUAL BELI NARKOTIKA DENGAN UU SPPA - Laksmidari Khansa Bella Wisnu Wardani; Kristiyadi Kristiyadi (Verstek, 2023)
This article aims to find out the legal considerations used by Judges in deciding a narcotics case with a child who acts as an intermediary for buying and selling narcotics in the study of verdict Number 4/Pid.Sus-Anak/2022/PNWng. The method used in this research is normative legal research that is prescriptive and applied. The research approach uses a case approach. The types of legal materials used are primary legal materials and secondary legal materials with library research/ document studies. Based on the research, the results obtained were that the judge's considerations in deciding criminal cases with children as defendants were in accordance with the Law on Juvenile Justice System. Children Against the Law have fulfilled the elements of the article charged by the Public Prosecutor through evidence that is in accordance with Article 183 of the Criminal Procedure Code. In addition, the trial is also in accordance with the provisions of the Law on Juvenile Justice System where children are tried based on the Juvenile Criminal Justice System. However, in sentencing, the judge felt that he had not been optimal in his considerations where the judge still ruled out several articles and principles in the Law on Juvenile Justice System which affected the outcome of the decision in sentencing.Keywords: Children Against the Law; Narcotics Sale and Purchase Intermediary; The Law on Juvenile Justice System